THE INFLUENCE OF COMPETENCE ON EMPLOYEE PERFORMANCE WITH MEDIATION OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Janah, Indah Roikhatul; Racmansyah, Yanuar; Sutanto, Himawan Arif (Journal of Management and Islamic Finance, 2023)
Human resources (HR) are one of an organization's most important assets that contribute to the success and growth of an organization. The aim of this research is to analyze the influence of competency, job satisfaction and organizational commitment on employee performance, the mediating role of organizational commitment and job satisfaction on the relationship between competency and employee performance. The object of this research was the Tegal Regency Investment and One-Stop Integrated Services Service (DPMPTSP). The sampling technique was carried out with a saturated sample of 43 people. SEM-PLS analysis was used to analyze data using SmartPLS. The research results show that competency and organizational commitment have a positive and significant effect on employee performance. Competency has a positive and significant effect on job satisfaction and organizational commitment. Meanwhile, job satisfaction has no effect on employee performance. Organizational commitment is able to act as a mediator in the relationship between competency and employee performance. Employees who have good competence feel more confident and feel successful in doing their work so that they can increase positive feelings towards their organization which encourages increased organizational commitment through maximum effort in doing their work. However, job satisfaction is not able to mediate the relationship between competency and employee performance. If employee satisfaction is lacking, it can result in employees being less enthusiastic about doing their work.